Respostas

A melhor resposta!
2013-11-28T13:00:43-02:00
A) f(x) = x² - 7x + 6

Δ= (-7)² - 4.1.6
Δ= 49-24
Δ= 25

x= 7 + √25
          2.1

x= 7 + 5
      2 

x= 6

ou x= 7-5
           2
x= 1

b) g(x) = x² - 2x + 6

Δ= (-2)² - 4.1.6
Δ= 4-24
Δ= -20

Sendo Δ negativo, a função não terá raízes.
3 5 3
2013-11-28T13:03:26-02:00
f(x) = x² - 7x + 6
Δ=b²-4ac
Δ=(-7)²-4(1)(6)
Δ=49-24 =25
X=((-7)+-√25)÷2
x=6 e x=1

g(x) = x² - 2x + 6
Δ=(-2)²-4(1)(6)
Δ=4-24=-20
Como Δ é negativo, não existem raízes reais.




2 3 2